Amácio Mazzaropi in the Film and Culture of Brazil - Bueno, E. author. aut Link
XV, 196 p.
Keywords: Amácio Mazzaropi's work is a unique instance in Brazilian culture - as an artist not connected with the subsidized film industry, he developed a singular voice and represents a segment of the population usually either ignored or viewed with contempt by the established, experimental filmmakers.